Clinical utility of electrocardiographic voltage parameters for the diagnosis of hypertrophic cardiomyopathy - Li, Gui; Jin, Lingdan; Weng, Zhiyuan; Jin, Xueqing; Lin, Xiaoyan; Chen, Shuling (Frontiers in Cardiovascular Medicine, 2024)
Background: While electrocardiographic parameters of hypertensive left ventricular hypertrophy (H-LVH) are well known, limited data are available regarding hypertrophic cardiomyopathy (HCM). This study was to assess the diagnostic value of electrocardiographic voltage parameters in HCM. Methods: Included patients with HCM treated between March 2015 and May 2023. Voltage parameters (S-L, Cornell, Cornell product, Lewis, Peguero, and modified Cornell voltages) and echocardiography were evaluated. Receiver operating characteristic (ROC) curves were used to assess the diagnostic value of electrocardiogram in HCM. The multiple linear regression was conducted to analyze the correlation between electrocardiogram indicators and cardiac diastolic function. Results: The highest sensitivity for HCM was Peguero voltage (70.4%; 88.6% specificity). The Peguero voltage had high sensitivity in male (63.8%) and female patients (84.9%), those aged <65 years (71.6%) and >65 years (68.3%), with non-apical HCM (AHCM) (76.7%), obstructive HCM (82.1%), and non-obstructive HCM (66.9%). The sensitivity of the S-L voltage was high in AHCM (72.2%). The sensitivity for HCM reached 88.7% when the S-L and Peguero voltages were combined. The modified Cornell index had the highest area under the curve (0.88, 95%CI: 0.84-0.91), and its optimal cutoff value was 2.05 mV in males (77.6% sensitivity and 74% specificity) and 1.935 mV in females (90.6% sensitivity and 91.4% specificity). Peguero voltage (beta = 0.154, P =0.034) and SD (beta = 0.223 P =0.004) were independently correlated with E/e', an index of left ventricular diastolic function. Conclusion: The Peguero voltage had high sensitivity and specificity for detecting the presence of HCM. It was positively correlated with E/e' in patients with HCM. For AHCM, the S-L voltage was more advantageous. Combining the S-L voltage with the Peguero voltage further improves the sensitivity for HCM and thus could be used to improve the screening of HCM in clinical practice. The SD and modified Cornell voltage also had good diagnostic performance, especially in females.